Effect of Climate Change on the Hydrological Character of River Maros, Hungary-Romania - Sipos, György; Blanka, Viktória; Mezősi, Gábor; Kiss, Tímea; van Leeuwen, Boudewijn (Journal of Environmental Geography, 2014)
It is highly probable that the precipitation and temperature changes induced by global warming projected for the 21st century will affect the regime of Carpathian Basin rivers, e.g. that of River Maros. As the river is an exceptionally important natural resource both in Hungary and Romania it is necessary to outline future processes and tendencies concerning its high and low water hydrology in order to carry out sustainable cross-border river management. The analyses were based on regional climate models (ALADIN and REMO) using the SRES A1B scenario. The modelled data had a daily temporal resolution and a 25 km spatial resolution, therefore beside catchment scale annual changes it was also possible to assess seasonal and spatial patterns for the modelled intervals (2021- 2050 and 2071-2010). Those periods of the year are studied in more detail which have a significant role in the regime of the river. The study emphasizes a decrease in winter snow reserves and an earlier start of the melting period, which suggest decreasing spring flood levels, but also a temporally more extensive flood season. Changes in early summer precipitation are ambiguous, and therefore no or only slight changes in runoff can be expected for this period. Nevertheless, it seems highly probable that during the summer and especially the early autumn period a steadily intensifying water shortage can be expected. The regime of the river is also greatly affected by human structures (dams and reservoirs) which make future, more detailed modelling a challenge.